1981
DOI: 10.1017/s0016672300020486
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of two male recombination factors (MRF) isolated from a Southern GreekDrosophila melanogasterpopulation

Abstract: A comparative study of two male recombination factors (31.1 MRF and 23 .5 MRF) isolated from the same Southern Greek natural population, revealed specific differences in their activities. 23.5 MRF induces female sterility due to atrophic ovaries at a wide range of temperatures while 31.1 MRF does so only at high temperatures. The gross morphology of the atrophic ovaries was the same and unilaterally affected pairs were found in the F x of crosses with both 23 .5 and 31.1 MRF. Furthermore, 23 .5 MRF induces: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…However, the finding that P transposase recognizes internal sites on P element DNA (Kaufman et al 1989), while another protein interacts with the terminal inverted repeats (Rio & Rubin, 1988), suggests that non-P element-encoded proteins may be required for efficient transposition. This notion is further substantiated by genetic data showing that various ME laboratory strains respond differently to the dysgenic activities of the same P and hobo inducer strain (Stamatis et al 1981;Yannopoulos et al 1987;Daniels et al 1988).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the finding that P transposase recognizes internal sites on P element DNA (Kaufman et al 1989), while another protein interacts with the terminal inverted repeats (Rio & Rubin, 1988), suggests that non-P element-encoded proteins may be required for efficient transposition. This notion is further substantiated by genetic data showing that various ME laboratory strains respond differently to the dysgenic activities of the same P and hobo inducer strain (Stamatis et al 1981;Yannopoulos et al 1987;Daniels et al 1988).…”
Section: Introductionmentioning
confidence: 88%
“…(ii) 23-5A/CyL i MRF, a hobo strain established from a wild second chromosome isolated from the same natural population with 31-1/CyL 4 MRF in 1978. (Stamatis et al 1981).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports suggest that a female is GD sterile if she lays no eggs but normal if she lays one or more eggs which introduces a clear bias and conceals the range of variation displayed by this character in dysgenic crosses. A similar problem is encountered with the work of Stamatis et aL, (1981) where the same character is measured by the degree of ovarian atrophy. Although the authors clearly found quantitative variation they introduced three arbitrary and discontinuous classes in to this character, namely complete atrophy (A), reduced ovaries (R) and normal ovaries (N).…”
Section: Dxcussiomentioning
confidence: 94%
“…Λόγω της ιδιότητας αυτής ονομάστηκε στην αρχή παράγοντας ανασυνδυασμού στα αρσενικά (MRF: Male Recombination Factor) από τον Hiraizumi, που πρώτος απομόνωσε ένα άγριο χρωμόσωμα με αυτή την ιδιότητα (Hiraizumi 1971). Στη συνέχεια και άλλοι ερευνητές ανέφεραν την απομόνωση χρωμοσωμάτων με παρόμοιες ιδιότητες, από διαφορετικούς φυσικούς πληθυσμούς (Bucheton et al 1976, Yannopoulos and Pelecanos 1977, Stamatis 1981…”
Section: το στοιχείο ρ και το σύστημα δυσγενεσίας ρ-μunclassified